Genetic Features of Extended-Spectrum β-Lactamase-Producing Escherichia coli from Poultry in Mayabeque Province, Cuba - Michel Baez; Ivette Espinosa; Alexandra Collaud; Iliana Miranda; Damarys de las Nieves Montano; Angel L. Feria; Rosa Elena Hernández-Fillor; Dasiel Obregón; Pastor Alfonso; Vincent Perreten (MDPI AG, 2021)
A total of 434 poultry cloacal samples were collected from seven different farms in different years (2013-2015) in the Cuban province of Mayabeque and analyzed for the presence of third-generation cephalosporin-resistant Escherichia coli (3GC-R-Ec). Sixty-two 3GC-R-Ec isolates were recovered in total from the farms, with detection rates of 2.9% in 2013, 10.3% in 2014, and 28.7% in 2015. Characterization of 32 3GC-R-Ec isolates revealed the presence of the extended-spectrum β-lactamase (ESBL) genes blaCTX-M-1 (n = 27), blaCTX-M-15 (n = 4), and blaCTX-M-1 together with blaLAP-2 (n = 1). The isolates also contained different proportions of genes conferring decreased susceptibility to sulfonamides (sul1, sul2, sul3), trimethoprim (dfrA1, dfrA7, dfrA12, dfrA14, dfrA17), tetracyclines (tet(A), tet(B)), aminoglycosides (aac(6')-Ib-cr, strA, strB), chloramphenicol (cmlA1, floR), macrolides (mph(A), mph(D)), and quinolones (qnrS, qnrB, aac(6')-Ib-cr) as well as mutations in the fluoroquinolone-resistance determining regions of GyrA (S83L, D87N, D87Y) and ParC (S80I, E84G). The isolates belonged to 23 different sequence types and to phylogroups A (n = 25), B1 (n = 5), and D (n = 2), and they contained plasmid-associated incompatibility groups FII, X1, HI1, HI2, N, FIA, and FIB. These findings reveal a genetically diverse population of multiresistant ESBL-producing E. coli in poultry farms in Cuba, which suggests multiple sources of contamination and the acquisition of antibiotic resistance genes.